English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

The number after a variable in parentheses is the exponent

-2 (3x)2 (xy) (2x)2=

I got -24x5y but my book says it is -72x5y

PLEASE HELP ME!!

2007-06-27 06:52:17 · 6 answers · asked by Anonymous in Science & Mathematics Mathematics

6 answers

Since you have the 3x in parentheses, that means that both the 3 and the x gets the exponent, so 3 squared is 9. Likewise for the 2x squared, which equals 4(x^2). So altogether, you have:
-2 * 9(x^2) * xy * 4(x^2)
= -72x^5y
Hope this clears it up for you.

2007-06-27 07:01:18 · answer #1 · answered by Lee 3 · 0 0

-2 (3x)^2 (xy) (2x)^2=

remember PEMDAS:
distribute exponents when necessary,
-2(9x^2)(xy)(4x^2)=

multiply
-72x^5y

when multiply exponents, you add the exponents,
for x, since 2+1+2 = 5 the exponent for x is 5

2007-06-27 06:59:03 · answer #2 · answered by Carmen 4 · 0 0

(3x)² = 9x² and
(2x)² = 4x²

those multiply together to make 36x^4, and you multiply that by xy and -2 to get

-72(x^5)y

2007-06-27 07:00:43 · answer #3 · answered by Philo 7 · 0 0

-2 (3x)2 (xy) (2x)2
= -2 (9x2) (xy) (4x2)
= -72x5y

2007-06-27 06:59:47 · answer #4 · answered by grandpa 4 · 0 0

-2 (3x)^2 (xy) (2x)^2
=-2*9x^2*xy*4x^2
= -72x^5y...........-2*9*4 =-72

2007-06-27 06:59:15 · answer #5 · answered by harry m 6 · 0 0

it's been a while... but I don't see how either could be correct... are you sure you've written it correctly??

2007-06-27 07:03:09 · answer #6 · answered by bored at work 3 · 0 2

fedest.com, questions and answers